Review of nonopioid multimodal analgesia for surgical and trauma patients. (10th October 2020) - George, Stephy; Johns, Meagan
Abstract: Purpose: Pain is a frequent finding in surgical and trauma patients, and effective pain control remains a common challenge in the hospital setting. Opioids have traditionally been the foundation of pain management; however, these agents are associated with various adverse effects and risks of dependence and diversion. Summary: In response to the rising national opioid epidemic and the various risks associated with opioid use, multimodal pain management through use of nonopioid analgesics such as acetaminophen, nonsteroidal anti-inflammatory drugs, α 2 agonists, N -methyl-d -aspartate (NMDA) receptor antagonists, skeletal muscle relaxants, sodium channel blockers, and local anesthetics has gained popularity recently. Multimodal analgesia has synergistic therapeutic effects and can decrease adverse effects by enabling use of lower doses of each agent in the multimodal regimen. This review discusses properties of the various nonopioid analgesics and encourages pharmacists to play an active role in the selection, initiation, and dose-titration of multimodal analgesia. The choice of nonopioid agents should be based on patient comorbidities, hemodynamic stability, and the agents' respective adverse effect profiles. A multidisciplinary plan for management of pain should be formulated during transitions of care and is an area of opportunity for pharmacists to improve patient care. Conclusion: Multimodal analgesia effectively treats pain while decreasing adverse effects. There is mounting evidence to support use of this strategy to decrease opioid use. As medication experts, pharmacists can play a key role in the selection, initiation, and dose-titration of analgesic agents based on patient-specific factors.